2013
DOI: 10.1021/am402827g
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Nanotopography on Electrospun PLLA Microfibers Modifies RAW 264.7 Cell Response

Abstract: In this study, we created a new method of electrospinning capable of controlling the surface structure of individual fibers (fiber nanotopography). The nanotopographical features were created by a phase separation in the fibers as they formed. To control the phase separation, a nonsolvent (a chemical insoluble with the polymer) was added to an electrospinning solution containing poly-l-lactic acid (PLLA) and chloroform. The nanotopography of electrospun fibers in the PLLA/chloroform solution was smooth. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 71 publications
3
74
0
Order By: Relevance
“…However, there were no pores in Fig. 1a, because high proportional solvent inhibited phase separation during the electrospinning [26]. For further investigation, the fibers in Fig.…”
Section: Electrospinning Aligned Porous Fibersmentioning
confidence: 98%
“…However, there were no pores in Fig. 1a, because high proportional solvent inhibited phase separation during the electrospinning [26]. For further investigation, the fibers in Fig.…”
Section: Electrospinning Aligned Porous Fibersmentioning
confidence: 98%
“…Previously, it was shown that macrophage activation could be modulated by the topographical characteristics of biomaterials [15,16,28e30]. Some studies found nanofibers minimized the secretion of pro-inflammatory cytokines [15] while some showed cell-invasive microfibrous materials favored M2 phenotype and angiogenesis [16,29,30]. However, these studies were conducted in vitro for a relatively short period of time and the long-term effects of biomaterial architecture on FBR are unclear.…”
Section: In Vivo Biocompatibility Of Electrospun Pu Membranesmentioning
confidence: 99%
“…The distance between the needle and the rotating collector (22cm in diameter) was fixed at 5.5 cm, the voltage was held constant at 20 kV, and the humidity was maintained between 30% and 40%. Recently, the electrospinning apparatus was further optimized to control the humidity within 1–2% because uncontrolled humidity can place surface nanotopography onto the fibers which may influence cell behavior [Schaub et al, 2013]. …”
Section: Biomaterials Approaches Studied Within Experimental Models Ofmentioning
confidence: 99%